2002
DOI: 10.1103/physreve.65.046505
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear quantum regime of the x-ray Compton laser

Abstract: In this work a scheme of x-ray coherent radiation generation in the nonlinear quantum regime by means of mildly relativistic high density electron beams and a strong pump laser field is investigated. The consideration is based on a self-consistent set of Maxwell and relativistic quantum kinetic equations. The coupled equations are solved in the slowly varying envelope approximation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 21 publications
1
30
0
1
Order By: Relevance
“…This effect has been also proposed for the coherent X-ray generation due to the quantum reflection of an electron beam from a laser-field phase lattice [200] and for the monochromatization of charged-particle beams by a laser pulse [201]. It has recently been shown that this mechanism may be relevant for atom acceleration as well [202].…”
Section: Acceleration By Crossed and Two-color Laser Beamsmentioning
confidence: 95%
“…This effect has been also proposed for the coherent X-ray generation due to the quantum reflection of an electron beam from a laser-field phase lattice [200] and for the monochromatization of charged-particle beams by a laser pulse [201]. It has recently been shown that this mechanism may be relevant for atom acceleration as well [202].…”
Section: Acceleration By Crossed and Two-color Laser Beamsmentioning
confidence: 95%
“…Finally, we note that, adopting the same scaling of Eqs. (15)- (17) in Eq. (5), this can be interpreted as a Schrödinger equation for a single particle with a "mass"ρ 3/2 in a selfconsistent pendulum potential.…”
Section: Wigner Function Approachmentioning
confidence: 99%
“…This estimate is in agreement with Refs. [35,36]. The dense plasma exists for the duration of a laser pulse but vanishes almost completely after switching off the field.…”
Section: Photon Productionmentioning
confidence: 99%